The knowledge deficit : closing the shocking education gap for American children - Hirsch, E. D., Jr. (Eric Donald), 1928- (Boston : Houghton Mifflin, 2006)
Hirsch shows why American students perform less well than students in other industrialized countries. Drawing on classroom observation, the history of ideas, and current scientific understanding of the patterns of intellectual growth, he builds the case that our schools have indeed made progress in teaching the mechanics of reading, but do not convey the more complex and essential content needed for reading comprehension. Hirsch reasons that literacy depends less on formal reading 'skills' and more on exposure to rich knowledge. His argument gives parents specific tools for enhancing their child's ability to read with comprehension; shows how No-Child-Left-Behind tests and SATs are measuring a kind of knowledge that is not being taught in our schools; and maps out how American schools can become a strong antidote to poverty and to the race-based achievement gap, and thus fulfill our democratic ideal for our children.--From publisher description.
1. Why do we have a knowledge deficit? -- The achievement crisis -- The curse of romantic ideas -- Should schooling be natural? -- What about "mere facts"? -- Is knowing how better than knowing what? -- Is society to blame -- Making better ideas prevail -- 2. Sounding out : just the beginning of reading -- What we've recently achieved -- Is reading like listening? -- Filling in the blanks -- Are some kinds of knowledge better than others? -- Reading strategies : a path to boredom -- 3. Knowledge of language -- Learning the standard language -- Learning grammar -- Learning the elaborated code -- Building vocabulary -- Can disadvantaged children catch up? -- 4. Knowledge of things -- What the text doesn't say -- Who is the general reader? -- How much knowledge do we need? -- Which knowledge do we need? -- Why not in the reading program? -- 5. Using school time productively -- Wasting students' time -- Blaming teachers -- Better use of time leads to greater fairness -- Using time effectively -- 6. Using tests productively -- Are tests driving our schools? -- The flaws of state tests -- The nature of reading tests -- What kinds of tests will enhance education? -- 7. Achieving commonality and fairness -- Reading and a wider crisis -- Fulfilling our nation's highest ideals -- Constantly changing schools, a critical issue -- Localism and a perfect storm of bad educational ideas -- Are there decisive advantages in specifying definite content? -- Thinking the unthinkable : a core of common content in early grades -- Appendix. The critical importance of an adequate theory of reading.
Includes bibliographical references (p. 139-158) and index.
Keywords: Reading; Reading -- United States; Literacy -- United States; Education -- United States -- Philosophy